Komposisi Hasil Tangkapan Ikan dan Tingkat Keramahan Lingkungan Alat Tangkap Sero di Desa Tapulaga, Sulawesi Tenggara - Rita Bubun; Fajriah Fajriah; Nelly Marlisa (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2015)
The principle development fishing in substance lead to the use of resources to optimal and rational for fishermen society welfare, without causing damage resources, environmental and sustaineble fisheries. The cath that fesiable to get on operation